Relationship between Self-concept and Attitude towards the Others - Jafar Rezaei; Negin Salimi (Muṭāli̒āt-i Mudīriyyat-i Ṣan̒atī, 2004)
Attitude has been the focal point of studies for social psychologists for many years. A proper understanding of this concept can be helpful in many  fields  such  as  management  and  communication.  One's  attitude toward different issues stems from his relation with the issues. Thus, one's attitude towards himself is deeply rooted in his relationship with himself. Starting a new relationship brings about complexities to the process of the relationship. Negative attitude towards oneself and others causes serious problems in various organizations. On the other hand, positive attitude seems to be beneficial to the improvement of the organizational relationships. The object of this study is to elaborate  the concept of the attitude as well as test the following hypothesis: "there is a significant relationship between one's attitude towards himself and towards the others ".The results confirm the hypothesis.